Numerical and Experimental Studies of a Wet Multidisc Clutch on Temperature and Stress Fields Excited by the Concentrated Load. Issue 1 (2nd January 2019) - Yu, Liang; Ma, Biao; Li, Heyan; Liu, Jikai; Li, Mingyang
Abstract: The outer circlip constraint is a typical way for a wet multidisc clutch to limit the axial displacement of friction components. The pressure transmission mechanism in a clutch, excited by the concentrated reactive force of the outer circlip, is revealed by a simplified pressure calculation model. Moreover, a finite element model is constructed to investigate the contact pressure distributions on friction surfaces. Thermal analysis to determine the radial temperature distributions on friction surfaces is performed numerically. The computational results indicate that the concentrated reactive force contributes to the dissimilar distributions of the contact pressure along the radial and axial directions. The radial contact pressure considerably affects the temperature fields on friction surfaces, which is verified effectively by bench tests under the creeping condition. Both simulation and experimental results demonstrate that the outer circlip is identified to be one of the main reasons for the expansion of the radial temperature difference. In order to smooth the contact pressure in the radial direction, three new designs for a circlip are proposed, including an inner circlip, medial circlip, and both inner and outer circlips. Considering the utility and feasibility of the four cases, the design with both the inner and outer circlips is the most appropriate one.